2021
DOI: 10.1111/vde.13016
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events associated with venomous insect immunotherapy and clinical outcomes in 82 dogs (2002–2020)

Abstract: Background -Limited information is known on adverse events and efficacy associated with venomous insect immunotherapy (VIT) in canine patients.Objectives -To assess adverse events associated with VIT and perceived efficacy of VIT.Animals -Records from 82 client-owned animals which received VIT were assessed.Methods and materials -A retrospective review of records from 2002 to 2020. Clinical history, adverse events during therapy and observations following field stings were collected from all records. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Anaphylaxis to conventional VIT induction has been reported previously in one dog in a retrospective study involving 28 dogs 26 . In another retrospective review of conventional and maintenance VIT in 82 dogs, anaphylaxis was not reported as an adverse reaction during any stage of VIT 10 . Systemic adverse reactions to VIT in people are rare and reported to occur more frequently during the induction phase of VIT compared to the maintenance phase 27,28 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Anaphylaxis to conventional VIT induction has been reported previously in one dog in a retrospective study involving 28 dogs 26 . In another retrospective review of conventional and maintenance VIT in 82 dogs, anaphylaxis was not reported as an adverse reaction during any stage of VIT 10 . Systemic adverse reactions to VIT in people are rare and reported to occur more frequently during the induction phase of VIT compared to the maintenance phase 27,28 .…”
Section: Discussionmentioning
confidence: 98%
“…9 No standard VIT induction schedules exist for dogs and as a consequence, most veterinary dermatologists adopt protocols that have been designed for use in people. 10 Rush VIT in people appears to be safe, with infrequent severe adverse reactions. 8,11 Mild adverse reactions reported in children are limited to local cutaneous reactions which occur with similar frequency during rush (19%) and conventional VIT (23%).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations